Increased expression of CysLT2 receptors in the lung of asthmatic mice and role in allergic responses. (April 2018) - Matsuda, Masaya; Tabuchi, Yuki; Nishimura, Kazuma; Nakamura, Yuri; Sekioka, Tomohiko; Kadode, Michiaki; Kawabata, Kazuhito; Nabe, Takeshi
Highlights: CysLT2 receptors were constitutively expressed in murine lung, and expression was strengthened in asthmatic mice. Activation of CysLT2 receptors was functionally involved in allergic leukocyte infiltration into the lung. The CysLT2 receptor can be a molecular target for the development of new pharmacotherapies for asthma. Abstract: Compared with CysLT1 receptors, the functional role of CysLT2 receptors in asthma has not been clarified. The purpose of this study was to determine 1) whether CysLT2 receptors are expressed in the lung of mice and if expression increases in asthmatic mice, and 2) whether CysLT2 receptors are involved in allergic leukocyte infiltration into the lung and in the development of airway remodeling in asthmatic mice. BALB/c mice were sensitized with ovalbumin (OVA) + Al(OH)3, and intratracheally challenged with OVA 4 times. Lung tissue was isolated before and after the 4th OVA challenge for detection of CysLT2 receptors by immunohistochemistry and flow cytometry. The effect of a CysLT2 receptor antagonist BayCysLT2 RA on multiple antigen challenge-induced leukocyte infiltration into the lung and the development of airway remodeling was evaluated. Even in non-challenged mice, CysLT2 receptors were expressed in bronchial smooth muscle. After multiple challenges, expression was also observed in leukocytes infiltrating into alveolar spaces. CysLT2 R + leukocytes included alveolar macrophages, conventional dendritic cells, and eosinophils. BayCysLT2 RA significantly inhibited multiple antigen challenge-induced increases in eosinophils and mononuclear cells in the lung. The development of airway remodeling was tended to be suppressed by CysLT2 receptor antagonist. In conclusion, CysLT2 receptors were constitutively expressed in the lung, and expression was strengthened in asthmatic mice. Activation of CysLT2 receptors was functionally involved in allergic leukocyte infiltration into the lung. The CysLT2 receptor can be a molecular target for the development of new pharmacotherapies for asthma.